Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Differential Equations, Frobenius' Method

  1. Nov 22, 2011 #1
    1. The problem statement, all variables and given/known data

    Find the indicial roots of the following Differential Equation: xy'' - y' + x3y = 0

    2. Relevant equations

    y = Ʃ[n=0 to infinity]cnxn+r
    y' = Ʃ[n=0 to infinity](n+r)cnxn+r-1
    y'' = Ʃ[n=0 to infinity](r+r)(n+r-1)cnxn+r-2

    3. The attempt at a solution

    Plugging these values into the differential equation, I got

    xr{Ʃ[n=0 to infinity](n+r)(n+r-1)cnxn-1 - Ʃ[n=0 to infinity](n+r)cnxn-1 + Ʃ[n=0 to infinity]4cnxn+3} = 0

    The three sums must produce the x to the same exponent, so I tried pulling out the first 4 terms of the first two sums, so the three sums would each output x3 as their first term [the first two sums starting from n=4]. However, this left me with the following equation:

    r(r-1)c0x-1 - rc0x-1 + r(r+1)c1 - (r+1)c1 + (r+1)(r+2)c2x - (r+2)c2x - (r+2)(r+3)c3x2 - (r+3)c3x2 + [remaining sums] = 0.

    How do I solve for r with this equation? I don't know how to find the roots.

    [the solution to the DE is y=c1cos(x2) + c2sin(x2)
    Last edited: Nov 22, 2011
  2. jcsd
  3. Nov 22, 2011 #2


    User Avatar
    Homework Helper

    So you have
    [tex] x^3y = \sum_{n=0}^{\infty} c_n x^{n+r+3}[/tex]
    [tex] y' = \sum_{n=0}^{\infty} c_n (n+r)x^{n+r-1}[/tex]
    [tex] xy'' = \sum_{n=0}^{\infty} c_n (n+r)(n+r-1)x^{n+r-1}[/tex]

    so lets shift the equations, so they have the same form for powers of x, as follows:

    lets leave the 2nd & 3rd leave unchanged, but replace the 1st so the terms match, first replace n with m
    [tex] x^3y = \sum_{m=0}^{\infty} c_m x^{m+r+3}[/tex]
    then let m=n-4, which when m=0 gives n=4, subtituting in gives
    [tex] x^3y =\sum_{n=4}^{\infty} c_{n-4} x^{n+r-1} [/tex]

    Putting this all together we get
    [tex] \sum_{n=4}^{\infty} c_{n-4} x^{n+r-1}- \sum_{n=0}^{\infty} c_n (n+r)x^{n+r-1}+ \sum_{n=0}^{\infty} c_n (n+r)(n+r-1)x^{n+r-1}=0[/tex]

    Now lets group terms
    [tex] \sum_{n=0}^{3} c_n(- (n+r)+ (n+r)(n+r-1))x^{n+r-1}+
    \sum_{n=4}^{\infty} (c_{n-4} - c_n (n+r)+ c_n (n+r)(n+r-1))x^{n+r-1}=0[/tex]

    Now the indicial equation is given by the lowest power of x, this occurs when n=0
    Last edited: Nov 22, 2011
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook